The Correlation Between Sugar Level Values in Patients with DM and the Incidence of Skin Fungus in the Skin Clinic of Bhayangkara Hospital Lumajang - Indahati, Munik Tri; Suhari, Suhari; Addiarto, Widya; Abidin, Zainal (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
DM is a group of metabolic diseases with characteristics of hyperglycaemia that occurs due to abnormalities in insulin secretion, insulin action or both. Skin sugar levels constitute 55% of blood sugar levels in ordinary people. In patients with diabetes, the ratio increases to 69-71% of blood glucose that has been elevated. The purpose of this research is to determine the correlation between sugar level values in patients with dm and the incidence of skin fungus in the skin clinic of Bhayangkara Lumajang hospital.This study was a quantitative study with a r etrospective design, and is a type of correlational research. The sample size was 41 patients with total sampling technique. Data were collected by observing patient medical record data from January 2022 - December 2023 and using an instrument in the form of a checklist, then the data were analysed using the Spearman rank test. According to the results, the majority of patients (63,4%) had high blood sugar levels when they checked into the Skin Clinic, and the majority of patients (58,5%) had skin events meeting severe criteria. The results of the analysis test showed a Sig.(2-tailed) = 0.000 < 0,05 and r (correlation coefficient) = +0,701, meaning that there is a relationship between blood sugar values in patients with DM and the incidence of skin fungus in the Dermatology Clinic of Bhayangkara Lumajang Hospital. As an effort to improve the quality of services at the skin clinic, this research requires support from management in the form of a standard operating procedure so that every patient diagnosed with skin fungus is also checked for blood sugar considering that there is a strong relationship between sugar levels and the incidence of skin fungus